Persistent deficiencies in the measurement and reporting of tobacco use in contemporary genitourinary oncology clinical trials. (June 2022) - Zhao, Calvin; Myrie, Akya; Feuer, Zachary; Roberts, Timothy; Sherman, Scott E.; Bjurlin, Marc A.; Matulewicz, Richard S.
Abstract: Smoking is a causal or contributory factor for nearly all genitourinary cancers and exerts significant influence on treatment, quality of life, and survival outcomes. In order to understand the influence smoking has on the outcomes of contemporary therapies, pertinent smoking-related data must be systematically collected and report. We sought to determine how often and how rigorously smoking status is collected and reported in publications of clinical trials in genitourinary cancers by conducting a systematic review. Our initial search yielded 622 articles, 354 of which met criteria. The vast majority of included studies (91.8%) did not report any details about trial participants' smoking status. When included, 96.3% of studies reported baseline status qualitatively. No studies used a validated measurement instrument or reported change in participants' smoking status over the study period. Absence of the collection and reporting of smoking-related data precludes further study of how smoking impacts outcomes and highlights an important deficiency in GU oncology clinical trial design. Highlights: Tobacco-related GU cancers are common and there is a known interaction between smoking and patient outcomes. In this systematic review of late phase GU cancer clinical trials, smoking status was infrequently collected and reported. Improving tobacco use data collection and reporting in clinical trials will enhance our understanding of these important interactions.